No Association Between Maternal Dietary Protein Intake and Offspring Insulin Sensitivity Measures in the First Two Years of Life. (29th May 2020) - Allman, Brittany; Fuentes, Eva; Williams, D Keith; Turner, Donald; Børsheim, Elisabet; Andres, Aline
Abstract: Objectives: Findings of an association between maternal dietary protein intake (1.1–1.7 g·kg −1 ·day −1 ) close to requirements for pregnant women throughout gestation (1.22–1.52 g·kg −1 ·day −1 ) and offspring insulin sensitivity are mixed, perhaps as a result of the small spread in protein intake and the large gap between measurements (∼9–40 years). Therefore, our objective was to evaluate the association between a wider spread of dietary protein intake during pregnancy and measurements of insulin sensitivity in the offspring in early life. Methods: Healthy women ( n = 182, mean ± SD; BMI: 26.2 ± 4.2 kg/m2) were recruited early in pregnancy (<10 weeks). Dietary protein intake was assessed using a 3-day food record in early (∼10 weeks, EP) and late (∼30 weeks, LP) pregnancy. Offspring blood was sampled at 12 and 24 months, and the updated homeostatic model assessment of insulin resistance (HOMA2-IR) was computed using fasting glucose and insulin. Body composition was measured using nuclear magnetic resonance. Two linear models were fitted to the data to estimate: 1) the unadjusted relationship of maternal protein intake to offspring HOMA2-IR and 2) the relationship of maternal protein intake to offspring HOMA2-IR adjusted for maternal plant protein intake and BMI, and offspring sex and body fat percentage. Values are mean ± SD. Results: Habitual protein intake (average of early and late pregnancy measurements range: 0.5–1.9 g·kg −1 ·day −1 ) decreased throughout pregnancy (EP: 1.09 ± 0.36; vs. LP: 0.97 ± 0.28 g·kg −1 ·day −1, P = 0.0003). Offspring HOMA2-IR did not change from 12 (0.8 ± 0.8) to 24 (0.8 ± 0.9) months. Simple regression analysis: EP dietary protein intake did not associate with HOMA2-IR at 12 (β = 0.153, P = 0.429) and 24 (β = −0.349, P = 0.098) months. Similarly, LP dietary protein intake did not associate with offspring HOMA2-IR at 12 (β = 0.023, P = 0.916) and 24 (β = −0.442, P = 0.085) months. Results remained unchanged after multiple regression analyses were conducted. Conclusions: Maternal dietary protein intake (amount or type) during pregnancy is not associated with indirect measurements of insulin sensitivity in offspring during the first two years of life. Funding Sources: United States Department of Agriculture Agricultural Research Service Project 6026-51, 000-012-06S, and NIH/NIDDK R01 DK107516.